Disciplining Feminism From Social Activism to Academic Discourse - Messer-Davidow, Ellen (Duke University Press, 2002)
How was academic feminism formed by the very institutions it originally set out to transform? This is the question Ellen Messer-Davidow seeks to answer in Disciplining Feminism. Launched thirty years ago as a bold venture to cut across disciplines and bridge the gap between scholarly knowledge and social activism, feminism in the academy, the author argues, is now entrenched in its institutional structures and separated from national political struggle.Working within a firm theoretical framework and drawing on years of both personal involvement and fieldwork in and outside of academe, Messer-Davidow traces the metamorphosis of a once insurgent project in three steps. After illustrating how early feminists meshed their activism with institutional processes to gain footholds on campuses and in disciplinary associations, she turns to the relay between institutionalization and intellectualization, examining the way feminist studies coalesced into an academic field beginning in the mid-1970s. Without denying the successes of this feminist passage into the established system of higher learning, Messer-Davidow nonetheless insists that the process of institutionalization itself necessarily alters all new entrants-no matter how radical. Her final chapters look to the future of feminism in an increasingly conservative environment and to the possibilities for social change in general.Disciplining Feminism's interdisciplinary scope and cross-sector analysis will attract a broad range of readers interested in women's studies, American higher education, and the dynamics of social transformation